β1-Adrenergic Receptor Contains Multiple IAk and IEk Binding Epitopes That Induce T Cell Responses with Varying Degrees of Autoimmune Myocarditis in A/J Mice - Basavalingappa, Rakesh H.; Massilamany, Chandirasegaran; Krishnan, Bharathi; Gangaplara, Arunakumar; Rajasekaran, Rajkumar A.; Afzal, Muhammad Z.; Riethoven, Jean-Jack; Strande, Jennifer L.; Steffen, David; Reddy, Jay (Frontiers in Immunology, 2017)
Myocarditis/dilated cardiomyopathy (DCM) patients can develop autoantibodies to various cardiac antigens and one major antigen is β1-adrenergic receptor (β1AR). Previous reports indicate that animals immunized with a β1AR fragment encompassing, 197-222 amino acids for a prolonged period can develop DCM by producing autoantibodies, but existence of T cell epitopes, if any, were unknown. Using A/J mice that are highly susceptible to lymphocytic myocarditis, we have identified β1AR 171-190, β1AR 181-200 and β1AR 211-230 as the major T cell epitopes that bind major histocompatibility complex class II/IAk or IEk alleles, and by creating IAk and IEk dextramers, we demonstrate that the CD4 T cell responses to be antigen-specific. Of note, all the three epitopes were found also to stimulate CD8 T cells suggesting that they can act as common epitopes for both CD4 and CD8 T cells. While, all epitopes induced only mild myocarditis, the disease-incidence was enhanced in animals immunized with all the three peptides together as a cocktail. Although, antigen-sensitized T cells produced mainly interleukin-17A, their transfer into naïve animals yielded no disease. But, steering for T helper 1 response led the T cells reacting to one epitope, β1AR 181-200 to induce severe myocarditis in naïve mice. Finally, we demonstrate that all three β1AR epitopes to be unique for T cells as none of them induced antibody responses. Conversely, animals immunized with a non-T cell activator, β1AR 201-220, an equivalent of β1AR 197-222, had antibodies comprising of all IgG isotypes and IgM except, IgA and IgE. Thus, identification of T cell and B cell epitopes of β1AR may be helpful to determine β1AR-reactive autoimmune responses in various experimental settings in A/J mice.